Mature women’s attitude toward fashion photographs - Hor-Meyll, Luis Fernando; Pinto Godoy Jr., Geraldo (Review of Business Management, 2015)
Objective –To investigate the influence of the cognitive age of upper-middle class mature women regarding their attitude towards photographs of articles of clothing, as a result of their identification with the model wearing them. Design/methodology/approach – Experiment with a sample of 164 women, aged 55- 70 years old, living in Rio de Janeiro. The questionnaire was were based on scales found in the literature. Theoretical foundation Cognitive age (Barak; Schiffman, 1981; Leventhal, 1997; Szmigin; Carrigan, 2000; Wray; Hodges, 2008; Amaro; Johann; Meira, 2007; Birtwistle; Tsim, 2005; Moschis, 2003; Moschis; Mathur, 2006) Mature woman and fashion (Schewe, 1988; Slongo et al., 2009; Thomas; Peters, 2009; Moschis, Lee, & Mathur, 1997; Young; Miller, 2006; Wilkes, 1992; Facenda, 2000; Holmlund; Hagman; Polsa, 2010; Szmigin; Carrigan, 2000). Mature woman and advertising (Moschis, 2003; Venkatesh et al., 2010; Nam et al., 2007; Kozar; Damhorst, 2008; Araujo, Casotti, Da Silva, & Pessôa, 2015) Findings – The identification with the model was greater when the respondent perceived her as being close to her own cognitive age (F(1, 162) =615.87, p=0.000). The attitude toward the collection was more positive when the respondent perceived the model as being closer to her own cognitive age (F (2, 162) =1074.55, p=0.000). Practical implications –The degree of the consumer’s identification is greater when the model appears to be the same cognitive age as the consumer. When the consumer believes that the model is close to her own cognitive age, her attitude toward the displayed item is more positive.